Dual-task performances can be improved in patients with dementia: a randomized controlled trial - Schwenk, Michael; Zieschang, Tania; Oster, Peter; Hauer, Klaus (Neurology, 2010)
Deficits in attention-related cognitive performance measured as dual-task performance represent early markers of dementia and are associated with motor deficits and increased risk of falling. The purpose of this study was to examine the effect of a specific dual-task training in patients with mild to moderate dementia.